Military chaplaincy in contention : chaplains, churches, and the morality of conflict - Todd, Andrew, 1961- (Burlington, VT : Ashgate, 2013)
Chaplaincy highlights the need for faith and society to re-engage with vital moral questions. Military chaplains continue to operate within the dynamic tension between faith communities, the armed services and society, offering a distinct moral presence and contribution. Drawing the reader into the world of the military chaplain, this book explores insights into the complex moral issues that arise in combat (especially in Afghanistan), and in everyday military life, These include the increasing significance of the Law of Armed Conflict and the moral significance of drones. Through the unique chaplain's eye view of the significance of their experience for understanding the ethics of war, this book offers clearer understanding of chaplaincy in the context of the changing nature of international conflict (shaped around insurgency and non-state forces) and explores the response of faith communities to the role of the armed services. It makes the case for relocating understandings of just war within a theological framework and for a clear understanding of the relationship between the mission of chaplaincy and that of the military.
Chaplaincy in contention / Andrew Todd -- Moral soldiering and soldiers' morale / Andrew Totten -- 'You've been silent, Padre' / Philip McCormack -- Terrorism and interrogation, as an issue for chaplains on operations / Peter Sedgwick -- The robotisation of war: an end to military virtues? / David Fisher -- The British churches and their chaplains: standing back to back and walking in opposite directions / Peter Howson -- 'O hear us when we cry to thee': liturgy in the current operational context / Jonathan Ball -- Just war: an ethic of principles or a principled ethic? / James Coleman -- Moral engagements: morality, mission and military chaplaincy / Andrew Todd with Colin Butler.
Includes bibliographical references (pages 169-180) and index.
Keywords: Military chaplains; Just war doctrine; War -- Moral and ethical aspects; Just war doctrine; Military chaplains; War -- Moral and ethical aspects